Breeding biology of the White-rumped Swallow (Tachycineta leucorrhoa; Hirundinidae) in a wetland: A comparative approach - Lorenzón, Rodrigo Ezequiel (2012)
We studied the reproductive biology of the White-rumped Swallow (Tachycineta leucorrhoa) in a colony of 50 nests boxes located in a wetland of the Paraná River, Santa Fe, Argentina between 2004 and 2006. The nest boxes were checked regularly and reproductive parameters, as well as morphological data of eggs and nestlings, were recorded. The species had an average clutch size of 4.7 eggs whose volumes and weight means were 2.04 cm 3 and 2.17 g. respectively. The incubation period averaged 15.9 days and decreased with the clutch size. The mean nestling period was 23.8 days. Clutch size, number of nestlings per nest and the nestling period decreased with the advance of the breeding seasons, while the incubation time increased. Breeding parameters showed a similarity with those reported for the population from Chascomús site, although the eggs were 5% heavier, the incubation period took one more day and the reproductive success was also higher. With the closely related species Tachycineta meyeni, the studied species showed a lower clutch size. Finally, considering another closely related species Tachycineta bicolor, the White-rumped Swallow showed the reproductive life history traits characteristic of species in the southern hemisphere. We provide new information for this species nesting on wetlands, a fact that contributes to the understanding of changes in the life history of the Tachycineta genus along the American continent.